Study of Osmotic Response of Crucian Carp Carassius auratus (L., 1758) Spermatozoa to Develop Their Cryopreservation Protocol - Puhovkin, Anton (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 291